Powder metallurgical fabrication of graphene reinforced near-eutectic Al-Si matrix composites: Microstructural, mechanical and electrochemical characterization - Akcamli, Nazli; Senyurt, Berk; Gokce, Hasan; Agaogullari, Duygu (Elsevier - Division Reed Elsevier India Pvt Ltd, 2022)
Al-10 wt% Si matrix composites reinforced with a few-layered graphene (FLG) were fabricated via a powder metallurgical route. FLG in varying amounts (0.25, 0.5, 1, 2, and 5 wt%) was incorporated into the Al10Si matrix via mechanical alloying (MA) for different durations in a high-energy ball mill. The mechanically alloyed (MAed) powders were consolidated by uniaxial pressing and pressureless sintering processes. The as-blended (non-MAed) and MAed powders and bulk composites were investigated comparatively in terms of microstructural, thermal, mechanical, tribological and corrosion properties. The MAed powders demonstrated refined and semi-equiaxed particle morphology with reduced crystallite size values. Additionally, the FLG/Al10Si composites exhibited advanced microstructural and mechanical properties by the contribution of MA and reinforcing particles compared to those of the as-blended and unreinforced matrix. The highest hardness and lowest wear rate values were obtained for the 4 h-MAed Al10Si-2FLG (138 HV and 6.485x10-4 mm(3)/N.m) and Al10Si-5FLG (178 HV and 7.456x10-4 mm(3)/N.m) composites. Moreover, the compressive strength of the Al-10Si matrix improved approximately by 50 and 20% via 0.5 and 2 wt% FLG addition, respectively. Also, lower corrosion resistance properties were observed for the FLG reinforced composites compared to the Al10Si matrix. (c) 2021 Karabuk University. Publishing services by Elsevier B.V.
Keywords: Al-Si alloy composites; Few-layered graphene (FLG); Mechanical/microstructural properties; Corrosion resistance